Direct and indirect effects of post-fire conditions on successional pathways and ecological processes in black spruce-Kalmia forests - Bloom, Robin G. (2001)
The goal of this thesis was to estimate the relative importance of the mechanisms by which forest stands of east-central Newfoundland are replaced by unproductive dwarf-shrub communities following wildfire. Sheep laurel (Kalmia angustifolia L.) is the dominant species of these heath communities and its proliferation after forest fires may initiate a retrogressive pathway rather than forest stand replacement. This problem is addressed in four chapters that evaluate the roles o f differential plant establishment success (Chapters I & II), availability o f limiting resources (Chapter III) and the availability o f canopy cover (Chapter IV) as factors affecting vegetation dynamics following catastrophic fire. The main findings of the research are (1) that at least part of the inhibition pathway is caused by physical limitations on regeneration niches for black spruce and that the biotic process of competition from Kalmia is a less proximate cause o f forest regeneration failure; (2) plant functional diversity and black spruce productivity are restricted spatially and physiologically by patterns in fire severity; (3) burned habitats dominated by Kalmia have suppressed species richness and functional diversity irrespective o f low and high concentrations o f limiting resources; (4) failure o f black spruce to re-colonize these sites and provide cover to Kalmia is associated with measurable reductions in soil microbial activity and herb abundance. A recurring theme among these chapters is the inconsistency between the pattern o f stand retrogression observed in eastern Newfoundland and general theoretical models of succession as they have developed in the ecological literature. As a result of these comparisons, this thesis supports the view that the prevailing models of succession fail to be generalizable across geographic and environmental gradients. In the eastern boreal forest, the factors of fire severity and restriction o f regeneration niches for successional species are the critical aspects of disturbance ecology which are not explicitly accounted for in existing successional models. Until general theories account for forces other than competition that potentially affect community structure, a unified theory of plant succession will remain elusive.